Natural frequencies evaluation on existing reinforced concrete bridges using microtremor testing - Idris, Nurul Shazwin (2019)
Most bridges in Malaysia do not take earthquake loadings into their structural design consideration. Structure constructed without the consideration of seismic design is generally more vulnerable to ground shaking during seismic event. Even though Malaysia is located on the stable Sunda shelf with low to medium seismic activity level, effects of tremors due to Sumatran earthquakes have been reported several times. Identification of natural frequencies is important to avoid bridge resonance which could happen when frequency of excitation coincides with a bridge natural frequency. Resonance can cause failure to bridges. Therefore, it is important for newly constructed and old bridges to be tested using simple dynamic test such as microtremor test in order to determine the natural frequencies of the bridges. Microtremor is also known as ambient vibration test. The test is a non-destructive test and easy to be conducted with less labor, time and cost. From the testing, „ambient‟ vibration excitation experienced by a structure under normal operating conditions can be determined. The aim of this study was to determine the natural frequencies of two different lengths of reinforced concrete bridges crossing Sungai Sembrong and Sungai Simpang Kiri. By using GEOPSY software, Fourier Spectra Amplitude Ratio (FSA) analysis used for determining bridge natural frequencies and Horizontal-To-Vertical-Spectra-Ratio (HVSR) analysis for ground natural frequencies, fo. The natural frequency results for Sungai Sembrong Bridge (70 meter) was 2.2 Hz and for Sungai Simpang Kiri Bridge (75 meter) was 2.0 Hz, while the ground natural frequencies were 1.4 Hz to 2.1 Hz at Sungai Sembrong and 1.0 Hz to 1.5 Hz at Sungai Simpang Kiri. The frequency values for both bridges were almost the same. The bridge with longer span length had a lower frequency value compared to the one with shorter span. The frequency results were verified by calculating and developing empirical equation from previous researchers and code of practice.